Perturbation of Maize Phenylpropanoid Metabolism by an AvrE Family Type III Effector from Pantoea stewartii. Issue 3 (29th January 2015) - Asselin, Jo Ann E.; Lin, Jinshan; Perez-Quintero, Alvaro L.; Gentzel, Irene; Majerczak, Doris; Opiyo, Stephen O.; Zhao, Wanying; Paek, Seung-Mann; Kim, Min Gab; Coplin, David L.; Blakeslee, Joshua J.; Mackey, David
Abstract : The virulence activity of an effector protein belonging to the widely conserved AvrE family is linked to its ability to cause system-wide reprogramming of phenylpropanoid metabolism in susceptible maize seedlings. Abstract: AvrE family type III effector proteins share the ability to suppress host defenses, induce disease-associated cell death, and promote bacterial growth. However, despite widespread contributions to numerous bacterial diseases in agriculturally important plants, the mode of action of these effectors remains largely unknown. WtsE is an AvrE family member required for the ability of Pantoea stewartii ssp. stewartii ( Pnss ) to proliferate efficiently and cause wilt and leaf blight symptoms in maize ( Zea mays ) plants. Notably, when WtsE is delivered by a heterologous system into the leaf cells of susceptible maize seedlings, it alone produces water-soaked disease symptoms reminiscent of those produced by Pnss . Thus, WtsE is a pathogenicity and virulence factor in maize, and an Escherichia coli heterologous delivery system can be used to study the activity of WtsE in isolation from other factors produced by Pnss . Transcriptional profiling of maize revealed the effects of WtsE, including induction of genes involved in secondary metabolism and suppression of genes involved in photosynthesis. Targeted metabolite quantification revealed that WtsE perturbs maize metabolism, including the induction of coumaroyl tyramine. The ability of mutant WtsE derivatives to elicit transcriptional and metabolic changes in susceptible maize seedlings correlated with their ability to promote disease. Furthermore, chemical inhibitors that block metabolic flux into the phenylpropanoid pathways targeted by WtsE also disrupted the pathogenicity and virulence activity of WtsE. While numerous metabolites produced downstream of the shikimate pathway are known to promote plant defense, our results indicate that misregulated induction of phenylpropanoid metabolism also can be used to promote pathogen virulence.